THE SOCIAL QUALIFICATION OF THE CHILDREN FOR SCHOOL IN THE OUT-OF-FAMILY CARE INSTITUTIONS - Vasechko, Lubova (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article „ The social qualification of the children for school in the out–of– family care institutions” is based on research results. It analyses children who are being brought up in out-of-family institutional care and looks at their social readiness for comprehensive school. Previous research results show that while being in out-of-family institutional care, a child’s development is delayed due to insufficient external stimulation. Although it provides the child with physical security and satisfies their basic needs, it cannot provide the most important aspects of development for a child - a close relationship with at least one adult who could captivate and become a trustee for several years. The article raises and analyses the conditions that affect the process of preparation for school.